Penggambaran Orang Timur Dalam Film Kaka Boss - Aurelia, Gabriella; Haloho, Heppy (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to analyze the portrayal of Eastern Indonesians in the film Kaka Boss using Charles Sanders Peirce’s semiotic approach. The research addresses the urgency of understanding how popular media constructs ethnic identity and influences public perception. A qualitative content analysis was conducted, focusing on visual, verbal, and symbolic signs representing Eastern Indonesian cultural values and social characteristics. The findings reveal five main representations: dominant figure, upholder of family values, proactive and creative individual, courageous conflict resolver, and symbol of resilience amid legal challenges. These portrayals shift outdated stereotypes toward a modern yet culturally rooted image. The study underscores the strategic role of film in shaping an inclusive and empowering social reality.